Clinicopathological Analysis of 14 Cases of Primary Pulmonary Lymphoepithelial Carcinoma - Yixuan FANG; Anzhe WANG; Lumin SHEN; Xiao YUAN; Yu KONG (Chinese Journal of Lung Cancer)
Background and objective Primary pulmonary lymphoepithelial carcinoma (PPLEC) is a rare form of lung malignancy, accounting for only 0.7% of all lung cancers. It is currently classified as a distinct subtype within squamous cell carcinomas. This study aims to explore the clinicopathological characteristics of PPLEC and its subtypes, with the objective of enhancing understanding and improving diagnostic accuracy for this disease. Methods A retrospective analysis was conducted on the clinical, pathological, imaging, and prognostic data of 14 patients diagnosed with PPLEC at the First Affiliated Hospital of Soochow University between February 2019 and June 2023. Results A total of 14 cases of PPLEC were identified, including 5 cases of the Regaud type, with ages ranging from 33 to 73 years, comprising 2 males and 3 females; and 9 cases of the Schmincke type, with ages ranging from 36 to 79 years, including 4 males and 5 females. Computed tomography (CT) scans consistently demonstrated soft tissue masses or nodular shadows. Reagud type mainly showed peripheral masses and Schmincke type mainly showed central masses. Pathological examination revealed tumor cells exhibiting syncytial-like growth, accompanied by lymphocytic infiltration and stromal fibrosis, with the Regaud type showing well-defined borders combined with granulomatous inflammation, while the Schmincke type exhibited indistinct tumor margins. Immunohistochemistry showed that CK, CK5/6, P40 and P63 were positive, and the Ki-67 index of Regaud type was lower than that of Schmincke type; notably, all 8 cases tested for programmed death-ligand 1 (PD-L1) were positive. Epstein-Barr virus-encoded RNA (EBER) in situ hybridization was positive in all instances. Among these cases, 6 underwent surgical treatment, and 8 received comprehensive therapy; by the end of the follow-up period, all 14 patients remained alive. Conclusion PPLEC is a rare form of malignant lung tumor associated with Epstein-Barr virus (EBV) infection. The Regaud and Schmincke subtypes display distinct imaging and pathological characteristics. In the early stages of the disease, surgical intervention is the primary treatment method; however, for advanced stages, a multimodal treatment approach is utilized, resulting in a relatively favorable prognosis. Immunotherapy represents a promising and effective treatment modality for patients with middle to advanced stage disease exhibiting high PD-L1 expression levels.